2016
DOI: 10.1185/03007995.2015.1128888
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging therapies in the management of diabetic foot ulcers

Abstract: The various drugs and therapies for the management of diabetic foot ulcers comprise antibiotics, neuropathic drugs, wound dressings, skin substitutes, growth factors and inflammatory modulators. The majority of these therapies target the treatment of diabetic foot ulcers to address the altered biochemical composition of the diabetic wound. However, no single treatment can be definitively recommended for the treatment of diabetic foot ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 137 publications
0
32
0
2
Order By: Relevance
“…DFU is a main reason for amputation and death among diabetic patients, moreover, the treatments for DFU lead to a heavy economic burden to the patients and their family. [ 18 ] Early detection and timely treatment may significantly improve life quality and outcomes of the patients. [ 19 ] There are 2 major reasons contributing to the occurrence of DFU: diabetic neuropathy and peripheral vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DFU is a main reason for amputation and death among diabetic patients, moreover, the treatments for DFU lead to a heavy economic burden to the patients and their family. [ 18 ] Early detection and timely treatment may significantly improve life quality and outcomes of the patients. [ 19 ] There are 2 major reasons contributing to the occurrence of DFU: diabetic neuropathy and peripheral vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice for this diagnostic is a piperacillin/tazobactam combination and linezolid. Specifically, for osteomyelitis associated with overlying DFI, there are currently no approved drugs [44].…”
Section: Systemic Antibiotic Therapymentioning
confidence: 99%
“…EGF was also used in several clinical studies in advanced DFUs, and its administration showed promising results in the formation of granulation tissue and the prevention of amputation in patients [56]. Intra-lesion injection of the recombinant form of EGF (rhEGF) directly at the site of the wound demonstrated a greater pharmacodynamic response in terms of granulation tissue growth and wound closure [44]; while PDGF-BB, FGFb, VEGF, and EGF were the most frequently used factors to improve the wound's healing time, there were also clinical trials studying growth factors in the context of infection management. For instance, G-CSF was used in patients with ulcers complicated by soft-tissue infection, but it did not show a benefit in the treatment of the infection or cure the ulcer.…”
Section: Growth Factorsmentioning
confidence: 99%
“…More than 10% of diabetic patients develop DFUs at some point in their lives [3]. Treatments for DFUs include various drugs [4], several types of wound dressing or skin substitutes such as Integra V R dermal regeneration template [5] and dermal replacement [6][7][8]. Wound dressings using nanotechnology have been developed as tissue-engineered scaffolds for skin [9].…”
Section: Introductionmentioning
confidence: 99%